Corporate Social Responsibility Practices at PEMEX (2022)
Nowadays, adopting an organizational approach focused on sustainable practices aimed at promoting the responsible use of resources can represent a competitive advantage for companies, which can thus keep costs low and reputation high. An example of a company that adopts this approach is Petróleos Mexicanos (PEMEX). For this research, an analysis of theexternal management structureof the company –whose Interest Groups includes indigenous communities, civil society, government, media, suppliers and customers—was carried out based on the information provided on its website. The evaluation of the organization’s performance in terms of its relationship with relevant stakeholders includes the annual reports provided by the company, using a matrix that includes the results obtained each year in terms of stakeholder management. The results showa decreasing tendency of the company on its investment in socially responsible practices, which contradicts the justification of such investment to promote and boost the competitive advantage of the company.